THE REFLECTION OF NUMBERS IN PAREMIOLOGY (Journal of Multidisciplinary Sciences and Innovations, 2025)
This article examines the semantic, cognitive, and cultural dimensions of numbers in Uzbek proverbs from a paremiological perspective. It highlights how numerical components in proverbs serve not only as quantitative indicators but also as symbolic, axiological, and cognitive-cultural markers that reflect the worldview, social experience, and linguistic traditions of the Uzbek people. Drawing upon the works of key Uzbek linguists, as well as modern cognitive theories such as conceptual metaphor theory, the study advocates for a deeper, interdisciplinary analysis of numerical proverbs. The research underscores the significance of numbers as structurally conservative yet semantically dynamic units within the Uzbek paremiological system.